NIR-II photo-accelerated polymer nanoparticles boost tumor immunotherapy via PD-L1 silencing and immunogenic cell death - Zhang, Tian (2025)
Immune checkpoint blockade (ICB) therapy is a widely favored anti-tumor treatment, but it shows limited response to non-immunogenic "cold" tumors and suffers from drug resistance. Photodynamic therapy (PDT), as a powerful localized treatment approach, can convert a "cold tumor" into a "hot tumor" by inducing immunogenic cell death (ICD) in tumor cells, thereby enhancing tumor immunogenicity and promoting tumor immunotherapy. However, the effectiveness of PDT is largely hindered by the limited penetration depth into tumor tissues. To address these issues, we proposed an all-in-one drug system with NIR-II photo-accelerated PDT effects, efficient immune checkpoint gene silencing, and a facile manufacturing process. The so-called all-in-one drug system comprises a multi-modal designed polymer PPNP and siRNA. PPNP is an amphipathic polymer that includes the near infrared-II (NIR-II) photosensitizer Aza-boron-dipyrromethene (Aza-BODIPY), a glutathione (GSH)-cleavable linker, and a cationic monomer derived from cholesterol. PPNP can self-assemble and efficiently load siRNA. Under laser irradiation, PPNP triggers a potent ICD cascade, causing the on-demand release of siPD-L1, reshaping the tumor's immunosuppressive microenvironment, effectively inhibiting the growth of various tumors, and stimulating the immune memory. This study represents a generalized platform for PDT and gene silencing, designed to modulate immune-related signaling pathways for improved anticancer therapy.